Cytokine Release Syndrome (CRS) and Nicotine in COVID-19 Patients: Trying to Calm the Storm - Gonzalez-Rubio, Jesus; Navarro-Lopez, Carmen; Lopez-Najera, Elena; Lopez-Najera, Ana; Jimenez-Diaz, Lydia; Navarro-Lopez, Juan D.; Najera, Alberto (Frontiers in Immunology, 2020)
SARS-CoV-2 is a new coronavirus that has caused a worldwide pandemic. It causes a severe acute respiratory syndrome (COVID-19), fatal in many cases, characterized by a cytokine release syndrome (CRS). Great efforts are currently being made to block the signal transduction pathway of pro-inflammatory cytokines in order to control this “cytokine storm” and rescue severe patients. Consequently, possible treatments for cytokine-mediated hyperinflammation, preferably within approved safe therapies, are urgently being searched to reduce rising mortality. One approach to inhibit proinflammatory cytokine release is to activate the cholinergic anti-inflammatory pathway through nicotinic acetylcholine receptors (α7nAchR). Nicotine, an exogenous α7nAchR agonist, is clinically used in ulcerative colitis to counteract inflammation. We have found epidemiological evidence, based on recent clinical SARS-CoV-2 studies in China, that suggest that smokers are statistically less likely to be hospitalized. In conclusion, we hypothesize that nicotine could constitute a novel potential CRS therapy in severe SARS-CoV-2 patients.